Safety and Efficacy of Hydroxypropyl Guar-Hyaluronic Acid Dual-Polymer Lubricating Eye Drops in Indian Subjects with Dry Eye: A Phase IV Study - Deborah Awisi-Gyau; Neha Kapur; Rajesh Parekh; Umesh Yeddula; Shreesha Kumar Kodavoor (Ophthalmology and Therapy)
Abstract Introduction This work aimed to evaluate the safety and efficacy of hydroxypropyl guar-hyaluronic acid (HPG-HA) dual-polymer lubricating drops in Indian subjects with dry eye disease (DED). Methods This prospective, open-label, single-arm, phase IV study was conducted in India. Inclusion criteria: Adults (18–65 years) with an average total ocular surface staining (TOSS) score ≥ 4, best-corrected visual acuity of ≥ 20/40 in each eye, tear break-up time (TBUT) ≤ 10 s, and dry eye questionnaire (DEQ-5) score ≥ 6. Subjects received the first dose of HPG-HA eye drops on day 1 and self-administered 1–2 drops four times daily for 90 ± 5 days. Primary endpoints: Frequency and characteristics of treatment-emergent adverse events (TEAEs) throughout the study and TOSS score at day 90. Secondary/other endpoints: Dry eye symptoms score (through dry eye questionnaire [DEQ-5]) and TBUT. Results Of 175 subjects, 36 (20.6%) had ≥ 1 TEAE, and 27 (15.4%) of this reported ≥ 1 mild drug-related TEAE (eye irritation [n = 9], eye pruritus [n = 8], blurred vision [n = 6], increased lacrimation [n = 4], ocular hyperemia [n = 3], and ocular discomfort [n = 1]). One subject discontinued due to TEAEs, and none led to drug interruptions. No serious adverse events were reported. The mean TOSS score reduced from day 1 (6.12 ± 1.69, OU [both eyes]) to day 90 (2.40 ± 1.97, OU). The mean DEQ-5 score reduced from day 1 (11.50 ± 2.27) to day 90 (5.50 ± 2.50). TBUT increased from day 1 (right eye [OD], 5.70 ± 1.94; left eye [OS], 5.70 ± 1.96) to day 90 (OD, 9.51 ± 3.08; OS, 9.63 ± 3.01). Conclusions HPG-HA dual-polymer eye drop was safe and effective in relieving signs and symptoms of DED over 90 days in Indian subjects. Trial Registration Clinical Trial Registry India, CTRI/2022/03/041175.